Does Bursa Malaysia overreact? - Ali, Norli; Md Nassir, Annuar; Hassan, Taufiq; Zainal Abidin, Sazali (EuroJournals Publishing, 2009)
Findings for the whole period from January 1987 to December 2006 reveal that loser has insignificantly becomes loser and winner has significantly reversed in the subsequent period. Arbitrage portfolio does not provide any significant abnormal return thus, not consistent with the overreaction hypothesis. This is due to the reason that Malaysian investors are overoptimistic. After controlling for size, both small and large stocks have significantly support the overreaction hypothesis even after adjustment for difference in risk. No evidence of January effect is reported during the period; however, there is evidence of Chinese New Year effect documented in the findings. The study also shows that Malaysian Stock Market overreacts prior to 1997 Asian Financial crisis. During the post crisis, the results are not consistent with overreaction hypothesis. One possible reason to this behaviour is that investors are more aware of the phenomenon and have altered their trading strategy. As a result, overreaction behaviour diminishes and stock market gradually becomes efficient in the post crisis. These findings suggest that stock overreaction behaviour in Malaysian stock market only benefited the short-term investors. However, when the strategy is based on a longer formation period such as 5-year formation period, long-term investors are able to earn significant positive abnormal returns.